On the relationship of energetic particle precipitation and mesopause temperature - F. Enengl; N. Partamies; N. Ivchenko; L. Baddeley (Annales Geophysicae, 2021)
Energetic particle precipitation (EPP) has the potential to change the neutral atmospheric temperature in the mesopause region. However, recent results are inconsistent, leaving the mechanism and the actual effect still unresolved. In this study we have searched for electron precipitation events and investigated a possible correlation between D-region electron density enhancements and simultaneous neutral temperature changes. The rotational temperature of the excited hydroxyl (OH) molecules is retrieved from the infrared spectrum of the OH airglow. The electron density is monitored by the European Incoherent Scatter Scientific Association (EISCAT) Svalbard Radar. We use all available experiments from the International Polar Year (IPY) in 2007–2008 until February 2019. Particle precipitation events are characterized by rapid increases in electron density by a factor of 4 at an altitude range of 80–95 km, which overlaps with the nominal altitude of the infrared OH airglow layer. The OH airglow measurements and the electron density measurements are co-located. Six of the 10 analysed electron precipitation events are associated with a temperature decrease of 10–20 K. Four events were related to a temperature change of less than 10 K. We interpret the results in terms of the change in the chemical composition in the mesosphere. Due to EPP ionization the population of excited OH at the top of the airglow layer may decrease. As a consequence, the airglow peak height changes and the temperatures are probed at lower altitudes. The observed change in temperature thus depends on the behaviour of the vertical temperature profile within the airglow layer. This is in agreement with conclusions of earlier studies but is, for the first time, constructed from electron precipitation measurements as opposed to proxies. The EPP-related temperature change recovers very fast, typically within less than 60 min. We therefore further conclude that this type of EPP event reaching the mesopause region would only have a significant impact ...